(untitled) (Revista de Ciências Agroveterinárias, 2006)
Laccopetalum giganteum of the family Ranunculaceae, well-known commonly as “pacra-pacra”, “pacra”, “pagra”, “huamanripa”, it’s an endemic plant that grows in the Andean high rocky regions of Ancash, The freedom, Amazons, Caja marca and San Martin from Peru; used from immemorial times to increase the fertility of the bovine livestock and for the faith healers to calm the bronchial affections and the villagers’ rheumatism, but one of the uses that better it’s attributed in the last times it’s to increase the fertility of people, attributions for which is very sought-after but that it has not still been proven scientifically th is characteristic. It is very narrow the relationship that there are between the villagers and this plant, since depends on her for the fecundity and eliminate of parasites of it’s livestock but they d on’t make anything to stop it’s pillaging. Still there are not formal studies since about the benefits that it can give to the humanity to help to the problem of the not fertility, the reports of the World Organization of the Health assure that enters 60 and 80 millions of even in the world they suffer of infertility and of this group 40% has to do with the woman’s complications. In this work we lift the voice then of alert this species it is exposed to the indiscriminate collection being also the only one in their gender, and it’s in danger of extinction without discovering their potentialities to the world, situation demonstrated by the samplings that have been made in Andean high different communities.